2019
DOI: 10.1111/gwmr.12309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ambient Temperature, Precipitation, and Groundwater Level on Natural Source Zone Depletion Rates at a Large Semiarid LNAPL Site

Abstract: Natural source zone depletion (NSZD) is increasingly being integrated into management strategies for petroleum release sites. Measurements of NSZD rates can be used to evaluate naturally occurring hydrocarbon (HC) mass losses, and provide a baseline for evaluating engineered recovery systems. Here, nominal saturated and unsaturated zone HC losses were quantified by groundwater sampling and ground surface CO2 effluxes approximately monthly over a 1‐year period. In addition, subsurface gas profiles and temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(61 reference statements)
2
4
0
Order By: Relevance
“…2016; Eichert et al. 2017; McAlexander and Sihota 2019) and aligns with steady rates observed in southern California (Mackay et al. 2018a).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…2016; Eichert et al. 2017; McAlexander and Sihota 2019) and aligns with steady rates observed in southern California (Mackay et al. 2018a).…”
Section: Resultssupporting
confidence: 76%
“…The stability of NSZD rates 6 months apart contrasts with seasonal variation observed at sites in the middle portion of the U.S. (Sihota et al 2016;Eichert et al 2017;McAlexander and Sihota 2019) and aligns with steady rates observed in southern California (Mackay et al 2018a). The primary weather component that varies at the site is precipitation, with rainfall (30 cm, on average; 45 cm in 2019) typically in the winter months and dry or foggy conditions the remainder of the year.…”
Section: Sitewide Nszd Characterizationsupporting
confidence: 66%
See 3 more Smart Citations